Nanoscale patterning by AFM lithography and its application on the fabrication of silicon nanowire devices - Sabar D. Hutagalung,; Kam, Chung Lew; Darsono, Teguh (Universiti Kebangsaan Malaysia, 2014)
Many techniques have been applied to fabricate nanostructures via top-down approach such as electron beam lithography. However, most of the techniques are very complicated and involves many process steps, high cost operation as well as the use of hazardous chemicals. Meanwhile, atomic force microscopy (AFM) lithography is a simple technique which is considered maskless and involves only an average cost and less complexity. In AFM lithography, the movement of a probe tip can be controlled to create nanoscale patterns on sample surface. For silicon nanowire (SiNW) fabrication, a conductive tip was operated in non-contact AFM mode to grow nanoscale oxide patterns on silicon-on-insulator (SOI) wafer surface based on local anodic oxidation (LAO) mechanism. The patterned structure was etched through two steps of wet etching processes. First, the TMAH was used as the etchant solution for Si removing. In the second step, diluted HF was used to remove oxide mask in order to produce a completed SiNW based devices. A SiNW based device which is formed by a nanowire channel, source and drain pads with lateral gate structures can be fabricated by well controlling the lithography process (applied tip voltage and writing speed) as well as the etching processes.